The Effect of Motivation on Employee Performance with Organizational Culture as a Moderating Variable - Haedar Haedar; Apriyanti Apriyanti; Muhammad Kasran (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of motivation on employee performance with organizational culture as a moderating variable. This research was conducted at the Office of BPJS Health and Employment Palopo Branch. The sample of this study was 56 employees and was determined by the total sampling method. Data collection was done by using a questionnaire method. Hypothesis testing in this study using the Warp PLS 7.0 program. The results of this study indicate that motivation has a positive effect on employee performance. In addition, this study also shows the results that organizational culture strengthens the influence of motivation on employee performance.